2004
DOI: 10.1074/jbc.m402227200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization of the Interaction between Human La and Hepatitis B Virus RNA

Abstract: The La protein is a multifunctional RNA-binding protein and has also been suggested to be involved in the stabilization of hepatitis B virus (HBV) RNA. Here we demonstrate that antibodies against the human La protein specifically precipitate HBV RNA from HBV ribonucleoprotein-containing mammalian cell extracts, providing evidence for the association between human La and HBV RNA. Moreover, we report that the turnover of HBV RNA depends on structural features and less on the primary sequence of the La-binding si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(41 citation statements)
references
References 52 publications
(35 reference statements)
2
39
0
Order By: Relevance
“…It was reported previously that the La protein contributes to HBV pregenomic RNA stability through specific binding to the viral RNA, while cytotoxic T-lymphocyte (CTL) and interleukin-2 (IL-2) treatment results in the fragmentation of the La protein, which renders viral RNA vulnerable to degradation by cellular nucleases (5,13,14,16,44). To determine whether MyD88 induces the fragmentation of the La protein, we studied the expression of the La protein in MyD88-overexpressing cells by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported previously that the La protein contributes to HBV pregenomic RNA stability through specific binding to the viral RNA, while cytotoxic T-lymphocyte (CTL) and interleukin-2 (IL-2) treatment results in the fragmentation of the La protein, which renders viral RNA vulnerable to degradation by cellular nucleases (5,13,14,16,44). To determine whether MyD88 induces the fragmentation of the La protein, we studied the expression of the La protein in MyD88-overexpressing cells by Western blot analysis.…”
Section: Resultsmentioning
confidence: 99%
“…For these plasmids, the synthesis of the pregenomic RNA is driven by the cytomegalovirus (CMV) promoter and the Tet promoter, respectively. pCMV-HBV M2 is a derivative of pCMV-HBV in which the La protein-binding sites have been mutated (5). pCMV-HBV⌬PRE is a PRE deletion mutant of pCMV-HBV (15).…”
Section: Plasmids and Virusesmentioning
confidence: 99%
“…In addition to the well-described functions of the RNA-binding protein La in the processing of RNA polymerase III transcripts (for reviews, see Maraia, 2001;Wolin and Cedervall, 2002), the mammalian La interacts with both cellular (McLaren et al, 1997;Brenet et al, 2005) and viral mRNAs (Spangberg et al, 2001;Ehlers et al, 2004), and many reports suggest a role of La in regulation of cellular and viral translation. For instance, human La supports internal ribosome entry site (IRES)-and cap-dependent translation of viral mRNAs, such as hepatitis C virus, polio virus (Ali et al, 2000;Costa-Mattioli et al, 2004;Pudi et al, 2004), HIV TAR mRNA (Svitkin et al, 1994;Chang et al, 1995), suppresses translation of the hepatitis A virus (Cordes et al, 2008), and regulates IRES-and cap-dependent translation of cellular mRNAs (for example, BiP mRNA , X-linked inhibitor of apoptosis protein (Holcik and Korneluk, 2000), 5 0 TOP-mRNAs (Crosio et al, 2000) and Mdm2 mRNA (Trotta et al, 2003)).…”
Section: Introductionmentioning
confidence: 99%
“…However, we did not observe any cytotoxic effect in HepG2 cultures transfected with a plasmid expressing IDO (data not shown). In addition, the fact that overexpression of IDO does not affect the steady-state level of HBV pgRNA, for which the half-life is less than 12 h in cell cultures (11,68,69), plus the lack of effect on the steady-state content of cellular proteins, such as TDO and ␤-actin (Fig. 4, bottom, lane 3), strongly suggested that expression of IDO in HepG2 cells did not significantly affect the host cellular transcription and translation machinery but preferentially inhibited HBV protein and DNA biosynthesis.…”
Section: Ifn-␣ and Ifn-␥ Inhibit Hbv Replication In Human Hepatocyte-mentioning
confidence: 99%